Altered glycometabolism in zebrafish exposed to thifluzamide. (September 2017) - Yang, Yang; Liu, Wenxian; Li, Dongzhi; Qian, Le; Fu, Bin; Wang, Chengju
Abstract: Thifluzamide exerts toxic effects to zebrafish and causes liver mitochondrial damage. To better understand the further mechanism, adult zebrafish were exposed to a range of thifluzamide concentrations (0, 0.019, 0.19, and 1.90 mg/L) for 28 days. In response to 1.90 mg/L exposure, liver glycogen significantly increased and blood glucose decreased. The expression of genes related to glycometabolism showed corresponding changes. Genes related to mtDNA replication and transcription and genes participating in mitochondrial complexes showed altered expression, which might lead to the inhibition of the tricarboxylic acid cycle (TCA). Additionally, the activity of glucose-6-phosphate dehydrogenase (G6PDH) was markedly increased at 1.90 mg/L, which might result in the activation of the pentose phosphate pathway. Moreover, the activity of lactate dehydrogenase (LDH) was significantly reduced at 1.90 mg/L, which might indicate that anaerobic glycolysis was inhibited. This study suggests that the altered gene expression and enzyme activities might be responsible for changes in glycometabolism, as evidenced by the altered expression of glycometabolism-related genes, the increased amount of glycogen in the liver and the decreased blood glucose levels. Overall, thifluzamide caused dysfunctional glycometabolism and led to events that might contribute to various thifluzamide-induced abnormalities in zebrafish. Highlights: Thifluzamide increased liver glycogen levels in zebrafish. Thifluzamide reduced blood glucose levels in zebrafish. Aerobic glycolysis in liver was inhibited by thifluzamide. Anaerobic glycolysis in liver was inhibited by thifluzamide. Pentose phosphate pathway in liver was stimulated by thifluzamide.